Left-Sided Intracardiac Tumors in a Case of Widespread Vulvar Cancer - Nair, Raunak M. (JACC Case Rep, 2019)
Metastatic cardiac tumors associated with gynecological malignancies are rare. This report describes the case of stage-4 vulvar carcinoma that metastasized to the left ventricle of the heart. (Level of Difficulty: Intermediate.)